Profile of Parkia speciosa hassk metabolites extracted with SFE using FTIR- PCA method - Nik Abdul Rahman, Nik Norulaini; Zhari, Salman; Sarker, Md. Zaidul Islam; Ferdosh, Sahena; Che Yunus, Mohd. Azizi; Abdul Kadir, Mohd. Omar (Chung-Kuo Hua Hsueh Hui, 2011)
A rapid identification, classification and discrimination tool, using Fourier Transform Infrared (FTIR) spectroscopy combined with Principal Component Analysis (PCA), was developed and applied to determine the profile of the Supercritical Fluid Extraction (SFE) of Parkia speciosa seeds under various temperature and pressure conditions (313, 323, 333, 343, 353 and 363 K and 20.68, 27.58, 34.47, 41.37, 48.26, and 55.16MPa). The separation and identification of the compounds was carried out by Gas Chromatography coupled with Time of Flight Mass Spectrometry (GC/TOF-MS). This technique has made it possible to detect the variability obtained under different SFE conditions and the separation of different chemical compounds in P. speciosa seeds. The FTIR-PCA results were verified by GC/TOF-MS, and the FTIR-PCA method successfully identified the unsaturated carboxylic acids with the highest percentage area under the different conditions.